When will smart antennas be ready for the market? Part I. - Kaiser, T. (IEEE Signal processing magazine)
This work aims to shed more light on the issue of why smart antennas haven't yet penetrated the market despite all the research efforts that have been put into the technology. The paper looks at this issue from various perspectives and subdivides the discussions into fixed or nomadic and high mobility applications because of the different types of markets, demands, and technological barriers.